Biomedical and genetic characteristics of the Ryukyuans: demographic history, diseases and physical and physiological traits. (19th May 2019) - Koganebuchi, Kae; Kimura, Ryosuke
Abstract: Context: The Ryukyu Islands stretch across a southwestern area of the Japanese Archipelago. Because of their unique geographical and historical backgrounds, Ryukyuans have their own genetic and phenotypic characteristics, which have been disclosed in previous anthropological and biomedical studies. Objective: The history, peopling and biomedical and genetic characteristics of Ryukyuans are reviewed and future research directions are discussed. Conclusion: Morphological and genetic studies have suggested the complex demographic history of Ryukyuans and their relationships with other Asian populations. Knowledge of population formation processes is important to understand the distribution of pathogens. In viral infectious diseases, some strains that may be associated with disease symptoms are specific to Ryukyuans. Dramatic changes in diet have played an important role among Ryukyuans in terms of increases in lifestyle-related diseases and mortality risks. To achieve a better understanding of pathogenic disease factors, further integration of findings regarding the genetic and biomedical characteristics of the Ryukyuans is needed.